𝒩-Subalgebras in BCK/BCI-Algebras Based on Point 𝒩-Structures. (7th September 2010) - Jun, Young Bae; Kang, Min Su; Park, Chul Hwan
Abstract : The notion of𝒩 -subalgebras of several types is introduced, and related properties are investigated. Conditions for an𝒩 -structure to be an𝒩 -subalgebra of type( q, ∈ ⋁ q ) are provided, and a characterization of an𝒩 -subalgebra of type( ∈, ∈ ⋁ q ) is considered.